Intracellular Expression and Purification of a Recombinant Enzyme Involved in Bioconversion of Arteannuin B to Artemisinin in Escherichia coli Expression System - Sreenivasa Rao2, M. Lakshmi Narasu1*, Jyotheeswara Reddy Eedula1, Parcha (Recent Research in Science and Technology, 2011)
Streptomyces pactum produces an enzyme that converts Arteannuin B to Artemisinin that is an important antimalarial. The gene encoding this novel enzyme from Streptomyces pactum MTCC 3664 has been cloned and expressed in Escherichia coli BL21 (DE3). The enzyme is expressed in the form of inclusion bodies at 370C or in a soluble form at 280C. The recombinant enzyme was purified by Immobilized Metal Ion Affinity Chromatography (IMAC). The purified enzyme produced by constitutive expression was found to be functionally active as it showed the conversion of arteannuin B to artemisinin as detected by TLC and HPLC.